Performing health identities on social media: an online observation of Facebook profiles - Hunt, Daniel; Koteyko, Nelya (Elsevier, 2016)
The increasing role of online technology in mediating our accounts and experiences of health and illness is now well recognised. Whereas earlier research has examined the language of support groups and institutional websites, attention is increasingly turned to the uses of social networking sites/SNSs for health. Our study examines the role of Facebook in the lives of users with type 1 and type 2 diabetes and the multimodal discursive practices they employ in their ongoing representation of life with a long-term condition. Through the longitudinal observation of 20 individual Facebook profiles, we focus on the dynamics of our participants׳ interactions, the interactional activities they performed on Facebook (individual contributions, group contributions, and ׳likes׳), and the multimodal resources they used to achieve these. The analysis reveals Facebook users׳ sensitivity to the varied social contexts that are collapsed within their networks as well as the strategies they employ to perform publically acceptable identities. Salient multimodal actions performed by participants include constructing personal expertise in relation to diabetes management, displaying the individual׳s integration into wider diabetes-related networks, presenting mundane aspects of self-management verbally and visually, and adopting a playful stance. The analysis situates diabetes-related SNSs practices within the contexts of representation and production, problematizing optimistic policy and professional rhetoric that anticipates a Health 2.0 revolution.